What men want: Qualitative analysis of what men with prostate cancer (PCa) want to learn regarding genetic referral, counseling, and testing. Issue 5 (6th February 2020) - Greenberg, Samantha; Slager, Stacey; Neil, Brock O'; Cooney, Kathleen; Maughan, Benjamin; Stopa, Nicole; Venne, Vickie; Zickmund, Susan; Colonna, Sarah
Abstract: Background: Guidelines have changed recently to include genetic counseling (GC) and/or genetic testing (GT) for all men with aggressive prostate cancer (PCa). This study aimed to identify what information men with PCa desire before and from GC. Methods: Focus groups were conducted with men who have PCa. Audio recordings were analyzed for themes related to GT, the information they desired from health care providers, and implications for family members. Results: Thirty‐seven men with PCa participated in seven focus groups. Nearly all men felt GT was beneficial and impactful for their family and themselves. Most men were unaware of the risks to female relatives associated with hereditary cancer. Participants discussed that genetics should be incorporated at an appropriate time of their diagnostic journey. Conclusion: This study showed that men valued GC and GT for personal and familial implications, and often did not associate PCa genetics with risk for female relatives to develop cancer. Consideration should be given to the GC timing in regard to where men are in their treatment process. Providers referring patients can leverage patient motivations and utilize their relationship with the patient to determine the appropriate timing and personalize discussion with the patient regarding GC and GT.